Obspack N2O time-series result from Hyltemossa (70.0 m) - Michal Heliasz; Tobias Biermann; Meelis Molder; ICOS RI (Integrated Carbon Observation System, 2025)
This data file contains high accuracy European ObsPack observational timeseries in netCDF format of ambient mole fraction of n2o in dry air collected at Hyltemossa (70.0 m). The measurements were calibrated using the WMO GAW calibration scale NOAA-2006A. Included are (all whenever available) historical PI QCed data, ICOS Level 2 data, ICOS FastTrack data and ICOS NRT data. It is part of the 2025.3 FastTrack update of the Globalview EU data product and is intended for use in carbon cycle inverse modeling, model evaluation, and satellite validation studies. Metadata for the full n2o product release are available at https://commons.datacite.org/doi.org/10.18160/NKFH-2P0Z. Please also visit http://www.gml.noaa.gov/ccgg/obspack/ for more information. If you use these data in your research, please consider citing the full ObsPack release that this file is part of (https://commons.datacite.org/doi.org/10.18160/46ST-DEVK).
ICOS RI, Heliasz, M., Biermann, T., Molder, M. (2025). Obspack N2O time-series result from Hyltemossa (70.0 m), 2025-05-19–2025-09-07, European ObsPack, https://hdl.handle.net/11676/HNyZMpFjzXlbpFMKAQC1wu5Y
Keywords: Carbon Portal; ICOS; N2O; NOAA-2006A; Obspack; atmospheric dry air n2o mole fraction; time series; time instant, UTC; time instant, UTC; quality flag; quality flag; data level (Obspack); data level (Obspack); standard deviation of gas mole fraction; standard deviation of gas mole fraction; ICOS mole fraction uncertainty metrics; ICOS mole fraction uncertainty metrics; N2O (dry air mole fraction); N2O (dry air mole fraction); Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap